2009
DOI: 10.1007/s11547-009-0446-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of myocardial bridging and correlation with coronary atherosclerosis studied with 64-slice CT coronary angiography

Abstract: MSCT-CA is a reliable, noninvasive method that is able to depict myocardial bridging and associated atherosclerotic plaque in the proximal segments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 30 publications
3
27
1
Order By: Relevance
“…987 35 (3.5%) Table 9 DISCUSSION: Iskandrian and others [9][10][11][12][13] in their studies of myocardial bridging mentioned that among patients undergoing coronary angiography, the reported prevalence of myocardial bridging is 1.7 percent (range 0.5 to 16 percent), which is almost always confined to the left anterior descending artery (LAD) where as the present study reveals it as 3.5% only confined to LAD as well. Mookadam et al [14] in coronary angiography of 14, 416 patients reported myocardial bridging in 1.57% of cases.…”
Section: Bridging Segments N = 35 (N %)supporting
confidence: 46%
“…987 35 (3.5%) Table 9 DISCUSSION: Iskandrian and others [9][10][11][12][13] in their studies of myocardial bridging mentioned that among patients undergoing coronary angiography, the reported prevalence of myocardial bridging is 1.7 percent (range 0.5 to 16 percent), which is almost always confined to the left anterior descending artery (LAD) where as the present study reveals it as 3.5% only confined to LAD as well. Mookadam et al [14] in coronary angiography of 14, 416 patients reported myocardial bridging in 1.57% of cases.…”
Section: Bridging Segments N = 35 (N %)supporting
confidence: 46%
“…Traditionally, the area under the MB has been considered to be spared from atherosclerosis, and the area just proximal to it has been considered to be prone to the development of atherosclerosis along with shear stress considerations. 10,[18][19][20] The high-pressure gradients may increase the local wall tension and stretch and induce endothelial injury and plaque fissuring with subsequent thrombus formation, which is supported by autopsy and clinical studies. 21 In addition, the atherosclerosis process in the segments proximal to ICA is subject to the complex hemodynamics caused by retrograde blood flow from the MB squeezing at systole.…”
Section: Discussionmentioning
confidence: 85%
“…Our previous pilot-study provided first observations to assess the association between MB and proximal atherosclerosis, with the relevant bias of inclusion of patients with known CAD and prior myocardial revascularizations [19]. The present study was designed to include only patients with suspected CAD and to assess the MB influence on coronary atherosclerosis distribution and pattern providing a comparison with a clinically similar group of patients without MB by means of CT-CA.…”
Section: Discussionmentioning
confidence: 99%
“…CT Coronary Angiography (CT-CA) allows the detection of significant coronary artery stenoses and provides a valid alternative to CCA in selected patient populations [6,7]. Recent studies demonstrated that MB may be displayed with 16-and 64-slice CT-CA [8][9][10][11][12][13][14][15][16][17][18] and that proximal atherosclerotic lesions could be associated [19]. In our study, a population of patients who underwent CT-CA according to current clinical indications [6,7] was reviewed for the presence of MB and segmental atherosclerotic pattern.…”
Section: Introductionmentioning
confidence: 99%